Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

An advanced multifunctional strategy - enabled triboelectric nanogenerator for efficient wind-energy harvesting - Bin Wang; Yan Gu; Yan Zhou; Yamei Liu; Ning Huang; Guangze Du; Xinyang Liu; Lingling Han; Huibo Zhao; Zhen Wang; Yingao Xue; Jieqiong Lin (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Zinc Fertilizer Application in Different Stages Changes the Accumulation and Remobilization of Zinc in Winter Wheat - Muhammad Fraz Ali; Yuxi Niu; Guoming Li; Lijuan Ma; Xiang Lin; Shubo Gu; Yong Han; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Revealing the role of Fe particle size in soft magnetic geopolymer for enhancing energy conversion in airport pavement induction heating - Gonghui Gu; Xinchi Xu; Jinsheng Han; Lin Wan-Wendner; Zhiji Gao; Rongze Fu; Chuanqing Fu; Tao Ma (Energy and Buildings, 2025)

Novel nanoceria in situ-derived porphyrin heterostructure enhanced electrochemiluminescent and colorimetric dual-mode detection of tetracycline residue in foods - Xueran Shi; Yingbo Cao; Lin Cong; Tiance Gu; Jing Wang; Qian Han (Food Chemistry, 2025)

Large-Scale Aerial Gamma Spectroscopy for Exploring Sandstone-type Uranium Deposits: A Case Study of Gexi Area, Inner Mongolia - Zhe Jiang; XiaoZhong Han; Zhongyue Lin; Hang Hu; Qiang Lai; Yi Gu; ZhaoJian Wu; Xin Zhao (Applied Geophysics, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

The impact of changing ambient population composition on crime during COVID-19 lockdowns - Xin Gu; Lin Liu; Su Yeon Han; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Applied Geography, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Probabilistic multi-hazard risk assessment of high-rise buildings subjected to concurrent earthquakes and strong winds - Qian-Qian Yu; Ling-Han Liu; Xiang-Lin Gu; Yao-Yao Zhang (Engineering Structures, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans, 2025)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Effects of COVID-19 on coastal and marine environments: Aggravated microplastic pollution, improved air quality, and future perspective - Yixuan Han; Xiang Gu; Chunye Lin; Mengchang He; Yidi Wang (Chemosphere, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

A study on the demographic differences in visual impact assessments of the external space of electric vehicle battery swapping stations - Lin Zhang; Chenping Han; Tao Gu; Guanjun Li; Xiwu Qi; Jingjing Zhao (Environmental Impact Assessment Review, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Identification of a fundamental cryoinjury mechanism in MSCs and its mitigation through cell-cycle synchronization prior to freezing - Brian H. Johnstone; Dongsheng Gu; Chieh-Han Lin; Jianguang Du; Erik J. Woods (Cryobiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Impact of Cold Spells on Ischemic Stroke Severity and Clinical Outcomes in Tianjin, China - Juanjuan Xue; Chanjuan Wei; Xiaoshuang Xia; Xuemei Qi; Yumeng Gu; Zhongyan Wang; Suqin Han; Lin Wang; Xin Li (Journal of Meteorological Research, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A short review of probabilistic slope stability analysis considering spatial variability of geomaterial parameters - Wengang Zhang; Xin Gu; Liang Han; Jiahao Wu; Zhiwei Xiao; Maoyi Liu; Lin Wang (Innovative Infrastructure Solutions, 2022)

Probabilistic stability analysis of embankment slopes considering the spatial variability of soil properties and seismic randomness - Wen-gang Zhang; Jia-hao Wu; Xin Gu; Liang Han; Lin Wang (Journal of Mountain Science, 2022)

Effect of lgals3a on embryo development of zebrafish - Kan Chen; Yuqi Fan; Jun Gu; Zhihua Han; Yue Wang; Lin Gao; Huasu Zeng; Chengyu Mao; Changqian Wang (Transgenic Research, 2021)

Near-field prediction of chemical hazard diffusion based on improved differential evolution algorithm and fireworks algorithm - Chaoshuai Han; Xuezheng Zhu; Jin Gu; Qinwen Zuo; Lin Chen; Yihao Shi (Environmental Monitoring and Assessment, 2021)

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock - Feng Yao; Yuan-qiang Lu; Jiu-kun Jiang; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2017)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

The Study of the Effect of Hedyotis diffusa on the Proliferation and the Apoptosis of the Cervical Tumor in Nude Mouse Model - Peiying Zhang; Bei Zhang; Juan Gu; Lin Hao; Fangfang Hu; Conghui Han (Cell Biochemistry and Biophysics, 2015)

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

Survivals of D. galeata in sub-tropical reservoirs: harmful effects of toxic cyanobacteria in food source - Bo-Ping Han; Xian Lin; Lamei Lei; Jiguang Gu (Ecotoxicology, 2012)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

Cadmium tolerance and accumulation by two species of Iris - Yu-Lin Han; Hai-Yan Yuan; Su-Zhen Huang; Zhi Guo; Bing Xia; Jiguang Gu (Ecotoxicology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)